2016
DOI: 10.1039/c6nr04085c
|View full text |Cite
|
Sign up to set email alerts
|

Engineering high refractive index sensitivity through the internal and external composition of bimetallic nanocrystals

Abstract: High refractive index sensitivity (RIS) of branched Au-Pd nanocrystals (NCs) is engineered through lowering the dielectric dispersion at the NC resonant wavelength with internal or external atomic % Pd. To our knowledge, these NCs display the highest ensemble RIS measurement for colloids with LSPR maximum band positions ≤900 nm, and these results are corroborated with FDTD computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
1
20
1
Order By: Relevance
“…It was observed that the transmittance value noticeably decreased and absorbance increased with the increasing thickness of the Au/Pd thin film due to the thickness effect, because more states are available for the photons to be absorbed in relatively thicker films. The obtained absorbance values are lower than the absorbance values of the same material in the literature (Smith et al, 2016).…”
Section: Ultraviolet and Visible Spectroscopy Studiescontrasting
confidence: 77%
“…It was observed that the transmittance value noticeably decreased and absorbance increased with the increasing thickness of the Au/Pd thin film due to the thickness effect, because more states are available for the photons to be absorbed in relatively thicker films. The obtained absorbance values are lower than the absorbance values of the same material in the literature (Smith et al, 2016).…”
Section: Ultraviolet and Visible Spectroscopy Studiescontrasting
confidence: 77%
“…24 Au/Pd octopods were especially shown to be highly valuable in sensing due to their large refractive index sensitivity. 18,25 Whereas synthesis design strategies of NP morphologies have made significant progress, 26 one important factor is often overlooked in these strategies. In order to preserve the carefully designed morphologies and functionalities, the stability of the NPs is of utmost importance.…”
mentioning
confidence: 99%
“…Among them Au/Pd octopods have proven to be interesting systems due to a large degree of synthesis control allowing for the tuning of their size, morphology, and composition. , Furthermore, the combination of a strong plasmonic material such as Au with a catalytically active material such as Pd holds promise for many applications such as plasmon-enhanced catalysis, , sensing, and surface-enhanced Raman scattering (SERS) . Au/Pd octopods were especially shown to be highly valuable in sensing due to their large refractive index sensitivity. , …”
mentioning
confidence: 99%
“…6,[12][13][14][15][16][17][18][19] Multi-component nanocrystals with controlled shape were engineered for bioimaging, biomedical, diagnostics, energy storage, environmental remediation, and sensing applications. [20][21][22][23][24][25] In particular, the element composition modifies the sensitivity of metal nanocrystals by affecting the plasmonic properties and so the refractive index. 26 Although synthesis techniques for single-crystalline metal nanoparticles with convex shape (regular polyhedron, rod, disk, etc.)…”
mentioning
confidence: 99%
“…Manipulation of atomic bonds is an established means toward the design of chemical or physical properties of materials at the nanoscale. The deformation of the crystalline lattice modifies the binding energy and the chemical activity and selectivity of metal nanocrystals. The lattice distortion of the nanocrystals is ruled by structural and microstructural features such as size, shape, and defects. ,, Control of nanocrystal shape is crucial to tailor the functionality of individual particles as well as to target collective phenomena in self-assembled superstructures. , Multicomponent nanocrystals with controlled shape were engineered for bioimaging, biomedical, diagnostics, energy storage, environmental remediation, and sensing applications. In particular, the element composition modifies the sensitivity of metal nanocrystals by affecting the plasmonic properties and the refractive index . Although synthesis techniques for single-crystalline metal nanoparticles with convex shape (regular polyhedron, rod, disk, etc. )…”
mentioning
confidence: 99%